2017
DOI: 10.1371/journal.pbio.2001421
|View full text |Cite
|
Sign up to set email alerts
|

Differential excitatory control of 2 parallel basket cell networks in amygdala microcircuits

Abstract: Information processing in neural networks depends on the connectivity among excitatory and inhibitory neurons. The presence of parallel, distinctly controlled local circuits within a cortical network may ensure an effective and dynamic regulation of microcircuit function. By applying a combination of optogenetics, electrophysiological recordings, and high resolution microscopic techniques, we uncovered the organizing principles of synaptic communication between principal neurons and basket cells in the basal n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(65 citation statements)
references
References 76 publications
(123 reference statements)
5
50
1
3
Order By: Relevance
“…The dendritic shafts of VIP+ INs were the main subcellular domain targeted by glutamatergic inputs, with similar density on both the proximal and distal compartments. However, the density of excitatory inputs received by VIP+ INs appears much lower compared with other INs, such as those expressing PV ( Smith et al, 1998 ; Gulyás et al, 1999 ; Andrási et al, 2017 ). One EM study of CR+ INs in the rat hippocampus revealed that they share a similar density of excitatory inputs to VIP+ INs ( Gulyás et al, 1999 ), thus suggesting that the glutamatergic innervation of VIP+ and CR+ INs significantly differs at least from PV+ INs.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The dendritic shafts of VIP+ INs were the main subcellular domain targeted by glutamatergic inputs, with similar density on both the proximal and distal compartments. However, the density of excitatory inputs received by VIP+ INs appears much lower compared with other INs, such as those expressing PV ( Smith et al, 1998 ; Gulyás et al, 1999 ; Andrási et al, 2017 ). One EM study of CR+ INs in the rat hippocampus revealed that they share a similar density of excitatory inputs to VIP+ INs ( Gulyás et al, 1999 ), thus suggesting that the glutamatergic innervation of VIP+ and CR+ INs significantly differs at least from PV+ INs.…”
Section: Discussionmentioning
confidence: 93%
“…One characteristic of BLA INs that has not been fully explored is its diversity. BLA INs vary significantly in their firing, molecular, and morphological properties, including axonal projections ( Spampanato et al, 2011 ; Capogna, 2014 ; Vereczki et al, 2016 ; Andrási et al, 2017 ). Similar to their neocortical and hippocampal counterparts, BLA IN subtypes may serve profoundly different roles in the spatiotemporal control of local network activity associated with different brain states and behavioral contexts ( Tremblay et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The neurons of this cortical CCK+ network are connected by both GABAergic synapses and electrical synapses, and this network is distinct from other interneuronal networks of PV+ and neurogliaform neurons (Hestrin & Galarreta, ). Likewise, networks of distinct subtypes of PV+ neurons interconnected by GABAergic synapses and electrical synapses have been described in the rodent BNC (Andrási et al, ; Muller et al, ; Woodruff & Sah, ). Since these amygdalar and cortical networks are always interconnected by both chemical and electrical synapses, it seems likely that CCK+ neurons in the monkey BNC may also be interconnected by both types of synapses.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, synapse‐like contacts of CCK+ axon terminals with somata and dendrites of other CCK+ neurons were common, indicating that there is a network of interconnected CCK+ neurons in the monkey BNC. These contacts have not been described in anatomical studies in rodents, although presumptive CCK to CCK synapses have been seen using antibodies to CB1Rs (Andrási et al, ). A similar interconnected network of large CCK+/CB1R+ basket cells has been described in the rodent neocortex (Galarreta, Erdélyi, Szabó, & Hestrin, ).…”
Section: Discussionmentioning
confidence: 99%
“…Both ultrastructural and electrophysiological studies have shown that the rodent BNC contains a network of PV+ interneurons interconnected by chemical and gap‐junctional electrical synapses (Muller et al, ; Woodruff & Sah, ). Applying a combination of optogenetics, electrophysiology, and high‐resolution microscopy allowed Andrási et al () to demonstrate that actually both PV+ and CCK+ basket cells form separate networks that are interconnected by chemical synapses and gap junctions. However, both types of basket cells synapse with PV+ AACs.…”
Section: Discussionmentioning
confidence: 99%